The increasing of odontoblast-like cell number on direct pulp capping of Rattus norvegicus using chitosan - Widyasri Prananingrum (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Pulpal perforation care with direct pulp capping in the case of reversible pulpitis due to mechanical trauma was performed with chitosan which has the ability to facilitate migration, proliferation, and progenitor cell differentiation. Purpose: The purpose of this study was to determine the increasing number of odontoblast-like cells in direct pulp capping dental care of Rattus norvegicus using chitosan for seven and fourteen days. Methods: Samples were molars of male Rattus norvegicus strain wistar, aged between 8–16 weeks, divided into two treatment groups, namely group I given chitosan and group II as a control group given Ca(OH)2. Those Rattus norvegicus’ occlusal molar teeth were prepared with class I cavity, and then chitosan and Ca(OH)2 were applied as the pulp capping materials. Afterwards, glasss ionomer cement type IX was used as a restoration material. Their teeth and jaw were then cut on the seventh day and the fourteenth day. Next, histopathological examination was carried out to observe the odontoblast like cells. All data were then analyzed by t test. Degree of confidence obtained, finally, was 95%. Results: The results obtained showed that the significant differences of odontoblast like cells on the seventh day observation was 0.001 (p = 0.001), and on the fourteenth day observation was 0.002 (p = 0.002). Conclusion: The number of odontoblast-like cells in direct pulp capping dental care of rattus norvegicus using chitosan is higher than the one using Ca(OH)2 for seven and fourteen days.Latar belakang: Perawatan perforasi pulpa pada kasus pulpitis reversible karena trauma mekanis bur dilakukan direct pulp capping dengan cara pemberian bahan secara topikal pada daerah perforasi. Kitosan memiliki kemampuan untuk memfasilitasi migrasi, proliferasi dan diferensiasi sel progenitor pulpa. Tujuan: Tujuan penelitian ini adalah untuk menentukan jumlah peningkatan odontoblas-like cell pada perawatan direct pulp capping gigi Rattus norvegicus menggunakan kitosan selama 7 dan 14 hari. Metode: Sampel adalah gigi molar Rattus norvegicus jantan strain wistar, berusia antara 8–16 minggu, dibagi menjadi 2 kelompok perlakuan yaitu kelompok I yang diberi kitosan dan kelompok II sebagai kontrol yang diberi Ca(OH)2. Oklusal gigi molar Rattus norvegicus dipreparasi kelas I kemudian kitosan dan Ca(OH)2 diaplikasikan sebagai bahan pulp capping. Glass ionomer cement tipe IX digunakan sebagai bahan restorasi. Gigi beserta rahang tikus dipotong pada 7 dan 14 hari. Pemeriksaan histopatologi dilakukan untuk mengamati odontoblas-like cell. Semua data dianalisis dengan uji t. Tingkat kepercayaan = 95%. Hasil: Hasil penelitian menunjukkan perbedaan yang signifikan dalam odontoblas like cell pada pengamatan hari ke-7 (p = 0,001) dan pengamatan hari ke 14 (p = 0,002). Kesimpulan: Jumlah odontoblas like cell pada perawatan direct pulp capping gigi Rattus norvegicus menggunakan kitosan lebih tinggi dibandingkan dengan Ca(OH)2 selama 7 dan 14 hari.